Pemberdayaan Siswa SMP Melalui Sains Entrepreneur Untuk Melatihkan Jiwa Kewirausahaan - Rahayu, Rina; Ismawati, Riva; Sholihah, Fahridhotul (Universitas Muhammadiyah Mataram, 2025)
Abstract: Indonesia is currently facing great challenges in developing the quality of education that is able to produce a young generation ready to compete in the era of globalisation. Lack of understanding and exposure to entrepreneurship, especially science-based ones, results in low student interest and motivation to develop entrepreneurial skills. Therefore, the purpose of this service activity is to provide assistance in empowering science knowledge into commercial products, students can make useful and valuable products, and can increase the entrepreneurial spirit in themselves. The method of activities carried out is divided into three stages, namely preparation, implementation, and evaluation activities. After assisting the empowerment of science knowledge, the results showed that students were very enthusiastic, active, and excited during the activities starting from delivering the material to making ecoprint products. Abstrak: Indonesia saat ini tengah menghadapi tantangan besar dalam mengembangkan kualitas pendidikan yang mampu mencetak generasi muda siap bersaing di era globalisasi. Kurangnya pemahaman dan paparan terhadap kewirausahaan, terutama yang berbasis sains, mengakibatkan rendahnya minat dan motivasi siswa untuk mengembangkan keterampilan kewirausahaan. Oleh karena itu tujuan kegiatan pengabdian ini untuk melakukan pendampingan pemberdayaan pengetahuan sains menjadi produk komersial, siswa dapat membuat produk yang bermanfaat dan bernilai jual, serta dapat meningkatkan jiwa kewirausahaan dalam dirinya. Metode kegiatan yang dilakukan dibagi menjadi tiga tahap yaitu kegiatan persiapan, pelaksanaan, dan evaluasi. Setelah melakukan pendampingan pemberdayaan pengetahuan sains, diperoleh hasil bahwa siswa sangat antusias, aktif, dan bersemangat selama mengikuti kegiatan mulai dari penyampaian materi hingga membuat produk ecoprint.